The Effect of Engagement in Digital Health Challenges and Gamification Features of Applications on Increasing Physical Activity Among Millennials in Jakarta - Widyaningsih, Heni; Arini, Rani Eka; Andiani, Paramita (West Science Social and Humanities Studies, 2025)
This study investigates the impact of participation in digital health challenges and the gamification features of mobile applications on increasing physical activity among millennials in Jakarta. With the rapid adoption of digital health platforms, gamification and interactive challenges have emerged as effective tools to encourage healthier lifestyles. A quantitative approach was employed using 150 respondents, selected from Jakarta millennials, who completed a structured questionnaire based on a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability testing, classical assumption tests, regression analysis, and hypothesis testing. The results indicate that both participation in digital health challenges and gamification features significantly and positively influence physical activity levels. Furthermore, simultaneous testing showed that both variables together exert a strong and significant effect. The findings highlight the importance of integrating gamified elements and health challenges in digital platforms to sustain motivation and promote long-term behavioral change. This research contributes to the literature on digital health interventions and provides practical recommendations for application developers, healthcare providers, and policymakers in promoting active lifestyles among millennials.